2023
DOI: 10.3389/fphar.2023.1165212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tanshinone IIA for myocardial ischemia/reperfusion injury in animal model: preclinical evidence and possible mechanisms

Abstract: Introduction: Tanshinone IIA (Tan IIA), the major active lipophilic ingredient of Radix Salviae Miltiorrhizae, exerts various therapeutic effects on the cardiovascular system. We aimed to identify the preclinical evidence and possible mechanisms of Tan IIA as a cardioprotective agent in the treatment of myocardial ischemia/reperfusion injury.Methods: The study quality scores of twenty-eight eligible studies and data analyses were separately assessed using the CAMARADES 10-item checklist and Rev-Man 5.3 softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Its additional cardiovascular effects include antioxidant activity ( Yan et al, 2021 ), anti-atherosclerotic effects (J. Wang et al, 2020a ; Wang et al, 2020b ), protection against myocardial I/R injury ( Li et al, 2023 ; Zhu et al, 2023 ), regulation of lipid metabolism ( Gao et al, 2021 ), anti-fibrotic effects ( Yan et al, 2022 ), vasodilation ( Fan et al, 2011 ), and potential anti-arrhythmic effects ( Shan et al, 2009 ), further demonstrating its multi-faceted role in promoting cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Its additional cardiovascular effects include antioxidant activity ( Yan et al, 2021 ), anti-atherosclerotic effects (J. Wang et al, 2020a ; Wang et al, 2020b ), protection against myocardial I/R injury ( Li et al, 2023 ; Zhu et al, 2023 ), regulation of lipid metabolism ( Gao et al, 2021 ), anti-fibrotic effects ( Yan et al, 2022 ), vasodilation ( Fan et al, 2011 ), and potential anti-arrhythmic effects ( Shan et al, 2009 ), further demonstrating its multi-faceted role in promoting cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…It has significant anti-inflammatory effects. It can increase coronary blood flow, improve microcirculation and protect vascular endothelial function by inhibiting inflammation ( 64 ). Xu et al ( 65 ) reported that the protective effect of baicalein on the heart is realized through its anti-inflammatory effect.…”
Section: Delaying the Development Of Cmvd By Modulating The Inflammat...mentioning
confidence: 99%
“…While, the components that dissolve in water are salvianolic acid A, salvianolic acid B, purple oxalic acid, and rosmarinic acid. Among these two categories, the fat-soluble component, tanshinone, is highly valued due to its minimal toxicity, high effectiveness, safety, and ability to produce various pharmacological actions that are against tumors ( Jin et al, 2021 ), inflammation ( Ye et al, 2020 ), myocardial ischemia ( Zhu et al, 2023 ), oxidative stress ( Wu et al, 2021 ) and thrombosis ( Feng et al, 2021 ), inhibit left ventricular hypertrophy ( Pang et al, 2014 ), dilate blood vessels ( Lu et al, 2021 ), resist atherosclerosis ( Wen et al, 2020 ), protect brain tissue ( Wang et al, 2022 ), improve microcirculation ( Qin et al, 2023 ), significantly inhibit pulmonary fibrosis ( Feng et al, 2020 ), and activate immunity ( Chen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%